Pengaruh Penerapan Standar Pelayanan Terhadap Minat Pembiayaan Produk BSM Implan Di Bank Syariah Mandiri Cabang Gorontalo - Sofhian Sofhian; Nur Shaffitri Hudodo (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2019)
This study aims to determine and analyze the effect of Service Standard Implementation (Self Appearance, Knowledge of Banking Products & Services, Standards to Communicate with Customers) to the Interests of BSM Implant Financing in Gorontalo Branch Syariah Mandiri Bank partially. And to find out and analyze the influence of the application of service standards (Self Appearance, Knowledge of Banking Products & Services, Standards for Communicating with Customers) on the Interest of BSM Implant Financing in the Bank Syariah Mandiri Gorontalo Branch simultaneously.This type of research is quantitative research. The population in this study were BSM Implan customers who were doing installments in the 2018 period. And the sample was 70 customers obtained from the BSM Implan 2018 installment customer population. The data collection method was the questionnaire method. This study uses a multiple regression analysis method. And has a significant level of 0.05.From the results of the partial test the self-appearance variable did not significantly influence the interest in financing BSM Implants in the Gorontalo's branch. The testing between knowledge variables of banking products and services to interest in BSM Implan financing showed that the knowledge of banking products & services had a positive and significant effect on interest BSM Implan financing at the Bank Syariah Mandiri branch of Gorontalo. The partial test results between the standard variables communicating with customers towards the interest of BSM Implan financing show that the standard variable communicating with customers does not have a significant effect on interest in financing BSM Implan in the Bank Syariah Mandiri branch. From the results of simultaneous testing (f test) between independent variables namely Self-Appearance, Knowledge of Products & Services, and Communicating with customers on the dependent variable namely interest in BSM Implant financing shows that simultaneously, independent variables, namely the Implementation of Service Standards (Self-Appearance, Knowledge of Banking Products & Services, Standards for Communicating with Customers) affect the dependent variable namely the interest in financing BSM Implants at the Bank Syariah Mandiri branch of Gorontalo. The determination coefficient shows the magnitude of the influence of the implementation of service standards on the interest in financing BSM Implan products to the Syariah Branch of Gorontalo branch of 0.392 or 39.2% and the rest is influenced by other factors.